Establishment of a Detecting Procedure and Analysis of CEBPA-TAD Genetic Mutation in Vietnamese Acute Myeloid Leukemia Patients - Huong, Bui Thuy; Phuong, Trinh Le; Yen, Pham Bao (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: Acute myeloid leukemia (AML) is caused by mutations leading to the loss of control over the proliferation and differentiation of leukocytes in the bone marrow. In Vietnam, studies focusing on the statistics, types, rate and molecular characteristics of common genetic mutations in AML patients are still limited. Identification of chromosomal mutation using the standard karyotyping techniques has assisted effectively AML diagnosis, however, in approximate 45% of AML cases, karyotyping analysis show normal cytogenesis due to abnormalities occurring at the molecular level.In this study, we focused on the establishment of a procedureto detect CCATT-enhancer binding protein α mutations in Transactivation domain region (CEBPA-TAD), which are considered poor prognostic factor for treatment. Using this procedure, one sample carrying a 17-nucleotide deletion in TAD1 domain resulting in a frameshift and a premature stop, was identified and confirmed by sequencing. From these results, we aim to continue screening a larger sample size to get more significant statistical data and investigate the correlation of CEBPA mutation status with clinical characteristic to assist prognosis and treatment.  Keywords: Acute myeloid leukemia (AML), CCAAT enhancer binding protein α (CEBPA), mutation.